A vision of history in the teachings of Primate Stefan Wyszyński - Ewa Czaczkowska (Studia Theologica Varsaviensia)
For Primate Stefan Wyszyński, the past of the nation was an important element creating the identity of the nation, on whose behaviour its future depended. Maintaining the memory of the history of the nation, which, in the primate’s thought, was constituted when Mieszko I was baptised in 966, was one of the priorities of Cardinal Stefan Wyszyński’s teaching. For this reason, it was also a part of the world-view dispute between the Primate and the communist authorities of postwar Poland, whose aim was to erase many pages of history from national memory or to give them a different meaning as a condition for creating a „new” society based on the Soviet model. In the evaluation of the past, falsified in the People’s Republic of Poland, the Primate used „his own domestic and national sense” and „proper evaluation of the spirit”. The theological perspective allowed the Primate to look at the painful and tragic pages of history, including the lost national uprisings, as a sacrifice modelled on the sacrifice of Christ, necessary for the resurrection of Poland. According to Primate Wyszyński, the history of the nation was a reservoir of values, co-shaped by faith and the Church, from which future generations could draw in the struggle to regain independence in 1918 and regain sovereignty.